Actuarial independence and managerial discretion - Kamiya, Shinchi (2021)
Appointed actuaries are responsible for estimating the largest liability on property–casualty insurance companies’ balance sheet. Actuarial independence is crucial in safeguarding accurate estimates, where this independence is self-regulated by actuarial professional institutions. However, professional conflicts of interest arise when appointed actuaries also hold an officer position within the same firm, as officer actuaries also face managerial incentives. Using a sample of U.S. insurers that employ in-house appointed actuaries from 2007 to 2014, we find evidence that officer actuaries have different reserving practices than nonofficer actuaries. This difference in reserving is associated with tax shielding and earnings management incentives. Results are consistent with managerial discretion dominating actuarial independence; they are economically significant and should be of concern to regulators and professional institutions.